Investigations on possibility of mass-trapping of Synanthedon myopaeformis Bkh. (Lepidoptera Sesiidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Mass-trapping males of S.myopaeformis can be an alternative method to chemical treatment in the control of its infestations. Preliminary experiments carried out with different traps show that the best results can be obtained by using funnel trap B baited with mg 10 of blend of (Z,Z)-3,13-ODDA+(Z,E)-3,13-ODDA (95%+5% respectively) (μg 10 released daily). This control activity can be increased by adding a small quantity of terpenyl acetate (g 1) to the pheromone.The precise position of traps in the habitat can have a substantial effect on the levels of trap catches. It has been demonstrated that in S.myopaeformis, the trap catch is highest when the traps are positioned near the top, in the sunny foliage of the apple trees.